Growing without parents: can the media build children’s foundation of a healthy and safe lifestyle habits? (2014)
The need to work and increase the economic status of families has resulted in both parents working for long hours and this has reduced quality time that should have been hitherto spent with their toddlers at home. Toddlers therefore are left with care givers or some forms of electronic media (television, movies, video games, cell phones, and computer networks) not only for entertainment but also for instruction. Electronic media have indeed assumed central roles in the daily lives of our toddlers and have become an alternative for practical learning. The effect of electronic media could be both positive and negative, on children's cognitive, social, and behavioural development. Most of the health and safety habits imbibed during the toddler years can be viewed as a set of habits that exist on a continuum developed and nurtured by parents. “Can the media replace parents in building healthy and safe lifestyle habits in children?” the answer is in the negative as this article reviewed the risks in exposing children to electronic media especially at their formative age without guidance. It concluded that it is important to minimize the negative outcome of electronic media on toddlers’ health. In recommendation parents need to spend more time with their toddlers to reverse the negative impact of electronic media and take the responsibility of initiating early healthy and safe lifestyle habits in their toddlers by serving as models and positive motivators.